2022
DOI: 10.3389/fmolb.2022.848105
|View full text |Cite
|
Sign up to set email alerts
|

PIWI-Interacting RNAs (piRNAs): Promising Applications as Emerging Biomarkers for Digestive System Cancer

Abstract: PIWI-interacting RNAs (piRNAs) are a novel type of small non-coding RNAs (sncRNAs), which are 26–31 nucleotides in length and bind to PIWI proteins. Although piRNAs were originally discovered in germline cells and are thought to be essential regulators for germline preservation, they can also influence gene expression in somatic cells. An increasing amount of data has shown that the dysregulation of piRNAs can both promote and repress the emergence and progression of human cancers through DNA methylation, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 100 publications
2
32
0
Order By: Relevance
“…PIWIL2 expression in tissue was also found to be associated with tumour pattern. These ndings are similar to those of previous studies, which found elevated expression throughout the initial phases of cancer, implying the signi cant role of PIWIL-RNAs in cancer development 29,31,32,37 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PIWIL2 expression in tissue was also found to be associated with tumour pattern. These ndings are similar to those of previous studies, which found elevated expression throughout the initial phases of cancer, implying the signi cant role of PIWIL-RNAs in cancer development 29,31,32,37 .…”
Section: Discussionsupporting
confidence: 91%
“…Signi cant increased level of PIWIL1 was reported for colon, bladder, and hepatocellular carcinoma. Expression of the four members of the PIWI proteins was viewed as distinct in tumour tissue when compared with the adjacent non-tumorous tissue 12,32 . PIWIL3 and PIWIL1 were assessed for expression levels by 33 in colorectal cancer, and had non-signi cant expression statistically.…”
Section: Discussionmentioning
confidence: 99%
“…RNAs are divided into coding RNAs (mRNAs) and non-coding RNAs based on whether they can encode proteins. Studies have shown that mRNAs account for less than 2% of the total genome, and more than 98% are ncRNAs, such as lncRNAs, miRNAs, circRNAs, small nucleolar RNAs (snoRNAs) [ 35 ], tRNA-derived small RNAs [ 36 ], and piwi-interacting RNAs [ 37 , 38 ]. At a time when ncRNAs were poorly understood, they were considered nonfunctional “junk” [ 39 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Except for the exosomal miRNAs, lncRNAs and circRNAs, some other ncRNAs, including tRNA-derived small RNAs [ 36 ] and piwi-interacting RNAs [ 37 , 38 ], also participate in tumorigenesis. Due to the lack of adequate literature, we do not make too much of an elaboration here.…”
Section: Function Of Exosomal Circrnas In Hccmentioning
confidence: 99%
“…To the best of our knowledge, no studies have been conducted on the profile of small non-coding RNA (sncRNA) in neonates born to pregnant women who test positive for SARS-CoV-2. These regulatory non-coding RNAs, in particular miRNA and piRNA, have been suggested as promising biomarkers and therapeutic targets, mainly due to their condition-and cell-specific expression, as well as their impact on the network of signaling pathways at epigenetic, transcriptional, and posttranscriptional levels [33][34][35][36][37]. The effect of SARS-CoV-2 on the host miRNA profile was only investigated in blood plasma and placenta of pregnant women infected with SARS-CoV-2 [38] or in blood plasma/serum of COVID-19 patients [39,40].…”
mentioning
confidence: 99%